264 Early Career Awardee: Supplementing omega-6. (7th December 2018) - Cooke, R
Abstract: Our research group investigated the impacts of supplementing Ca salts of soybean oil (CSSO), a source of omega-6 fatty acids (FA), on reproductive performance of beef cows. Two initial studies were conducted with Nelore (Bos indicus) cows grazing tropical pastures. Cows were assigned to fixed-time AI (FTAI) and supplemented or not with 100 g/d (as-fed basis) of CSSO, whereas supplementation regimens ranged from d -11 to 28 relative to FTAI. Overall, CSSO supplementation during the 21 d after FTAI increased (P < 0.01) pregnancy rates from 38.1% (623/1635 as pregnant/total non-supplemented cows) to 49.0% (843/1720 as pregnant/total CSSO-supplemented cows), and these outcomes were associated with enhanced early embryonic development and pregnancy establishment when omega-6 FA were supplemented. To verify this rationale, our group compared FA incorporation in grazing Nelore cows (n = 90) supplemented or not with CSSO (100 g/d; as-fed basis) after FTAI and slaughtered on d 19 of gestation. Supplementing CSSO increased (P ≤ 0.05) incorporation of linoleic acid and its omega-6 derivatives into plasma, endometrium, corpus luteum, and conceptus, whereas the same responses were not observed (P ≥ 0.25) for omega-3 FA. Complementing these findings, grazing Nelore cows (n = 100) were supplemented or not with CSSO (100 g/d; as-fed basis) after FTAI, and assigned on d 15 of gestation to transcervical uterine flush. Supplementing CSSO increased (P ≤ 0.04) conceptus length (2.58 vs. 1.15 cm) and mRNA expression of interferon-tau (21.0 vs. 5.1 fold change) and prostaglandin E synthase 2 (7.9 vs. 3.0 fold change), which are critical regulators of pregnancy establishment. Recently, these outcomes were validated in B. taurus beef cows consuming temperate forages. Pregnancy rates were greater (P = 0.01) in Angus cows receiving CSSO (100 g/d; as-fed basis) for 21 d after FTAI (60.2%; 226/383 as pregnant/total cows) compared with non-supplemented cows (51.7%; 193/388 as pregnant/total cows). Supplementing 100 g/d of CSSO to Angus × Hereford cows (n = 96) also increased (P = 0.05) mRNA expression of interferon-tau in d 15 conceptuses. Collectively, post-AI CSSO supplementation to B. indicus and B. taurus beef cows favors incorporation of omega-6 FA into maternal and embryonic tissues, which enhances interferon-tau synthesis by the conceptus and increases pregnancy rates to FTAI.